NETWORK MODEL AND ALGORITHM FOR SOLVING PROBLEM OF OPTIMUM THERMAL LOAD DISTRIBUTION AMONG HEAT-SOURCES OF ENTERPRISE HEATING SYSTEM - V. A. Sednin; A. D. Korznikov; А. V. Sednin; I. V. Masevich (Наука и техника)
The paper  presents an algorithm for optimization of thermal load distribution among heat-sources in the system of centralized heat supply. The algorithm can be used while elaborating plans for development of heat supply systems in cities and settlements.